2015
DOI: 10.1007/s00401-015-1529-6
|View full text |Cite
|
Sign up to set email alerts
|

Resident microglia rather than peripheral macrophages promote vascularization in brain tumors and are source of alternative pro-angiogenic factors

Abstract: Myeloid cells are an essential part of the glioblastoma microenvironment. However, in brain tumors the function of these immune cells is not sufficiently clarified. In our study, we investigated differential pro-angiogenic activities of resident microglia and peripheral macrophages and their impact on glioma vascularization and progression. Our data demonstrate stable accumulation of microglia/macrophages during tumor growth. These cells often interact with tumor blood vessels correlating with vascular remodel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
171
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 169 publications
(183 citation statements)
references
References 52 publications
11
171
1
Order By: Relevance
“…[37] Microglia is considered as the resident macrophage in the brain and the initial responders to tissue damage. [58] Microglia express receptors that respond to various stimuli that may as a consequence result in there activation. [59] A large number of studies indicate that microglia expresses different proteins and cytokines that display different role to express different function.…”
Section: Microglia and Neuroinflammationmentioning
confidence: 99%
“…[37] Microglia is considered as the resident macrophage in the brain and the initial responders to tissue damage. [58] Microglia express receptors that respond to various stimuli that may as a consequence result in there activation. [59] A large number of studies indicate that microglia expresses different proteins and cytokines that display different role to express different function.…”
Section: Microglia and Neuroinflammationmentioning
confidence: 99%
“…The pro-inflammatory state of activated microglia, or the M1 type classical activation state, can be cytotoxic to surrounding cells, and when unregulated can propagate tissue damage and cause secondary injury [32], [33]. Correspondingly, neuroinflammation is thought to be implicated in multifarious functions and pathological states in the CNS, including the modulation of neurogenesis and neuronal development [25], [34], [35], synaptic stripping and neuronal dysfunction [36], [37], and is now widely implicated in the pathogenesis and progression of many neurodegenerative disorders [38], [39], [40], [41], [42], [43], [44], [45]. Alternatively, an M2 microglial activation state is not neurotoxic, transiently conferring neuroprotection and anti-inflammatory properties in response to injury [46].…”
Section: Microglial Responses To Stressors In the Cnsmentioning
confidence: 99%
“…In response to angiogenic signals, pericytes initially dissociate and lose the capacity of suppressing endothelial proliferation. On the other hand, pericytes derive from precursors, such as mesenchymal stem cells (MSCs) or hematopoietic precursors, induced to differentiate by the tumor microenvironment [40] and by transforming growth factor-β (TGF-β) [10]. Their recruitment depends on matrix metalloprotease (MMP-9) produced by CD45+ cells via SDF-1/CXCR4 signaling [41,42] and VEGF released from the extracellular matrix.…”
Section: Discussionmentioning
confidence: 99%
“…Their recruitment depends on matrix metalloprotease (MMP-9) produced by CD45+ cells via SDF-1/CXCR4 signaling [41,42] and VEGF released from the extracellular matrix. It has been demonstrated that in mice with NG2 deficiency, as well as with collagen VI deficiency [43], the tumor growth is reduced, and that GSCs give rise to pericytes to support tumor growth and vessel function through remodeling PVN [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation